Efficacy of dexlansoprazole-based triple therapy for Helicobacter pylori infections. (September 2019) - Kuo, Chia-Jung; Chen, Chun-Wei; Le, Puo-Hsien; Hsu, Jun-Te; Lin, Cheng-Yu; Cheng, Hao-Tsai; Su, Ming-Yao; Lin, Chun-Jung; Chiu, Cheng-Tang
Background: Dexlansoprazole has been shown to be efficacious for the treatment of gastroesophageal reflux disease. However, there is a paucity of data about its efficacy for Helicobacter pylori eradication. The aim of this study was to evaluate the efficacy of dexlansoprazole for H. pylori eradication as triple therapy in real-world practice. Methods: Adult patients with endoscopically proven H. pylori related peptic ulcer diseases or gastritis were recruited for this study. The eradication status was assessed based on the results of the 13 C-urea breath test performed 4 weeks after treatment. According to the different treatment regimens, the patients were allocated to group A: Esomeprazole 40 mg b.i.d. + amoxicillin 1 g b.i.d. + clarithromycin 500 mg b.i.d. for 7 days; group B: Esomeprazole 40 mg q.d. + amoxicillin 1 g b.i.d. + clarithromycin 500 mg b.i.d. for 7 days, or group C: Dexlansoprazole 60 mg q.d. + amoxicillin 1 g b.i.d. + clarithromycin 500 mg b.i.d. for 7 days. Results: A total of 215 patients (49% males) were enrolled in this study, with a mean age of 55 years. The eradication rates in group A, B, and C were 94.7% (71/75), 89.6% (69/77), and 93.7% (59/63) ( p = 0.457), respectively. The adverse events were similar between the three groups ( p  = 0.068). Conclusions: This study suggests that dexlansoprazole-based triple therapy has an acceptable eradication rate for H. pylori infection.